What Are the Morals of Video Game Stories? A Content Analysis of the Most Popular Video Games. - Klimenko, Marina A.; Kapadia, Kevin; Andre, Gaillot Jr (Journal of Broadcasting & Electronic Media, 2023)
A content analysis of moral content in the most popular video game franchises with stories between 1996 and 2021 was conducted. The results of the study revealed that there were, on average, 19 moral themes per 3-hour gameplay, and more acts followed basic moral principles. Binding morals (with group loyalty) was the most frequently depicted moral domain; individualizing immoral acts received more negative evaluations. Most moral and immoral acts received no consequences. There was a significant increase in all moral domains from 1996 to 2021. The significance of the findings, as well as limitations and future directions, are discussed